2004
DOI: 10.4324/9780203629451.ch13
|View full text |Cite
|
Sign up to set email alerts
|

The economic impact of living wage ordinances

Abstract: Drawing upon both prospective and retrospective evidence, this paper reviews the economic effects of local living wage ordinances. I concentrate my attention on the higher costs these measures create for covered firms, as well as their budgetary implications vis-à-vis cities that adopt them. I also briefly review the effect that living wage laws have had on bidding environment for city service contracts. Based on a range of cost estimates associated with living wage laws, I then examine the adjustment channels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…An Economic Policy Institute study in 1998 concluded that "after four years in force, the Baltimore living wage increase did not result in any discernible job loss" ([2], p. 10). In fact, research by Card and Krueger corroborate studies by Neumark and Wascher that living wage or "higher minimum wage mandates do not behave in the manner predicted by competitive models and that average firm employment does not decline but may in fact increase slightly following minimum wage increases" ( [9], p. 6). The unemployed often fill positions that the formerly underemployed no longer need to make ends meet.…”
Section: Economic Implications Of a Living Wagesupporting
confidence: 67%
See 2 more Smart Citations
“…An Economic Policy Institute study in 1998 concluded that "after four years in force, the Baltimore living wage increase did not result in any discernible job loss" ([2], p. 10). In fact, research by Card and Krueger corroborate studies by Neumark and Wascher that living wage or "higher minimum wage mandates do not behave in the manner predicted by competitive models and that average firm employment does not decline but may in fact increase slightly following minimum wage increases" ( [9], p. 6). The unemployed often fill positions that the formerly underemployed no longer need to make ends meet.…”
Section: Economic Implications Of a Living Wagesupporting
confidence: 67%
“…If production costs increase one to two percent, companies may decide to absorb expenses rather than risk losing business ( [9], p. 24). Likewise, some effects of raising prices are minimal.…”
Section: Economic Implications Of a Living Wagementioning
confidence: 99%
See 1 more Smart Citation
“…But this literature has also made clear the limitations of these measures in terms of affecting large numbers of the working poor. Indeed, most studies of both proposed and enacted living wage ordinances find that these measures affect a very small number of private sector firms in a given locale, and that the benefits of higher wages are concentrated among a small fraction of the overall workforce within any given municipality (Brenner 2004).…”
Section: The Effects Of Living Wages On Firm Behavior: Theory and Eximentioning
confidence: 99%
“…In addition, while compensation strategy is important on its own, it is also closely related to other choices the firm makes. Decisions on compensation strategy can affect the firm as a whole and influence other decisions (Balkin & Gomez-Mejia, 1987; Brenner, 2004). Faced with higher wages, for example, a firm may compensate with raising prices, increasing sales, changing operational techniques, or raising productivity.…”
mentioning
confidence: 99%